Optimalisasi Proses Pendidikan Peserta Forum Silaturahmi Pondok Pesantren Melalui Peranan Persepsi dan Komunikasi: Studi Kasus di Kota Cilegon Provinsi Banten - Safiudin; M.A Tihami; Gunawan, Agus; Masfuah, Syifa (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2023)
Education plays a crucial role in the development of individuals and society. Meanwhile, in the context of forums, perception and communication are two things that are closely related to each other. Forums are places where individuals or groups can gather to discuss, share ideas, and exchange views on certain topics. In forums, perceptions can affect how individuals communicate, and vice versa, communication can affect individual perceptions. The use of good and adequate communication techniques in hospitality forums facilitates the exchange of ideas, experiences, and a deep understanding of the values ​​of Islamic education. Thus, this article emphasizes the importance of utilizing the role of perception and communication in Islamic boarding school friendly forums as a way to optimize the educational process, have a positive impact on personal, social and religious development, as well as contribute to the progress of society and the ummah as a whole. The purpose of this paper is to explore the effect of perceived organizational support and internal communication on work engagement. In this paper, analytical research is focused on analyzing the effectiveness of perception and communication in organizing friendly forums for Islamic boarding schools in Cilegon City, Banten Province. The method in this writing uses library research or also known as the library research method, where the process of collecting and analyzing data is carried out from written sources, such as books, journals, and electronic documents. The analysis process carried out in this paper serves as a process for understanding, evaluating, and synthesizing information from written sources such as books, journals, articles, and other documents, the analysis carried out in this study uses qualitative analysis techniques, this technique is used to identify themes, concepts, and patterns in the material presented. Qualitative analysis can also help describe the author's context, point of view, and interpretation.